2023
DOI: 10.1002/aelm.202300208
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ferroelectricity in Hf‐Based Ferroelectric Device with ZrO2 Regulating Layer

Abstract: HfAlO film-based ferroelectric memory is a strong contender for the next-generation nonvolatile memories. However, the remanent polarization intensity of HfAlO films is small compared to other Hf-based ferroelectric films at low annealing temperatures. In order to further improve the remnant polarization of the device, the ferroelectric memory with metal-ferroelectric-metal structure using ZrO 2 as the regulating layer (RL) is designed and fabricated. Experimental results show that the device with the ZrO 2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In contrast, noticeable diffraction peaks are detectable in the La:HfO 2 film after the insertion of ZrO 2 , suggesting that ZrO 2 insertion can facilitate the crystallization of La:HfO 2 and lead to an increased presence of the o-phase. This theoretical study validates that such increase in the o-phase composition is conducive to promoting the ferroelectric properties of the ferroelectricity in the HfO 2 -based ferroelectric device. ,, …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, noticeable diffraction peaks are detectable in the La:HfO 2 film after the insertion of ZrO 2 , suggesting that ZrO 2 insertion can facilitate the crystallization of La:HfO 2 and lead to an increased presence of the o-phase. This theoretical study validates that such increase in the o-phase composition is conducive to promoting the ferroelectric properties of the ferroelectricity in the HfO 2 -based ferroelectric device. ,, …”
Section: Resultssupporting
confidence: 73%
“…This theoretical study validates that such increase in the o-phase composition is conducive to promoting the ferroelectric properties of the ferroelectricity in the HfO 2 -based ferroelectric device. 35,37,38 To study the interlayer on the breakdown robustness of La:HfO 2 -based devices, the P−V characteristics at different voltages for both La:HfO 2 and HZH devices were performed. The operating waveform schematic is displayed in Figure 4a.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Among them, hafnium-based ferroelectric field effect transistors (FeFETs) have attracted a lot of attention due to their advantages such as scalability, 20 low power consumption, and fast response speed, and are potential candidates for implementing logic and storage in a single transistor. 21–23 Among the various doping elements, such as Zr, 24,25 Al 26,27 and La 28–30 etc. , the La atom has gradually become popular for researchers due to its large ionic radius, low electronegativity and strongest stabilizing effect on HfO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…been made to overcome this problem [6][7][8][9]. For example, Lomenzo et al revealed that the TaN/HfO 2 /Ge capacitor exhibited a larger remanent polarization P r and better endurance than TaN/HfO 2 /Si device due to the absence of interfacial layer formed on the Ge surface [10].…”
Section: Introductionmentioning
confidence: 99%